Mechanical Compliance for Product Design (2025)
This document serves as a brief introduction to my capstone project, offering a glimpse into its core concepts and process. While the project, as defined within the academic scope, has been successfully completed, its development will continue beyond the university framework. To access the full documentation of the work completed during the capstone project—along with ongoing updates, new iterations, and future applications—please visit mcpd.schematica.studio. Maintaining the project’s documentation on my personal website allows me to provide the most current insights as the project evolves in a professional setting.